The advances of DNA methylation in the liquid biopsy for the detection of lung cancer - Chen, Yuxuan; Peng, Shuang; Wang, Cailian (Frontiers in Oncology, 2025)
Lung cancer is the most common cancer in the world and the leading cause of cancer death. The absence of effective early detection is one of the major contributors to high mortality rate of lung cancer. Liquid biopsy has the potential to become as a new method for early detection of cancer due to its non-invasive nature, ease of access, and overall presentation of tumor. Liquid biopsy has garnered increasing attention for its role in early detection and tumor genome assessment through the examination of circulating tumor DNA (ctDNA) released by apoptotic or necrotic tumor cells. DNA methylation is a potential biomarker for liquid biopsy due to its early onset, cancer specificity, biological stability, and accessibility in bodily fluids. This review aims to present an overview of the process of DNA methylation, identify potential methylation gene targets, and explore the application of liquid biopsy in the detection of lung cancer.